Prominence of Maturity Stage on Seed Germination Behaviour of Popular Rice Varieties - RENUGADEVI J; R SIVAKALAI; R JERLIN; V VAKESWARAN; D KEERTHANA; R UMARANI (Seed Research, 2025)
Though rice is a well-studied crop in the context of crop improvement, many of the seed development parameters that are critical for crop establishment largely remain unexplored. The relevance of stage of seed maturity is one such important trait which has direct impact on seed quality and subsequent crop performance. The present study was conducted with twelve rice varieties to determine the germination behaviour based on the stage of crop maturity. The freshly harvested seeds during physiological and harvestable maturity stages were evaluated for seed germination and seedling vigour index as a measure of seed quality. There were significant differences in germination of all the varieties harvested at different maturity stages. Among the varieties, five varieties viz., ADT 36, ADT 37, ADT 38, CO (R) 50 and N 22 were found dormant immediately after harvest irrespective of the stage of maturity and the remaining seven varieties were non dormant.